"A PCMH mind and a PCMH heart": Patient, faculty, and learner perspectives on collaborative care in an interprofessional team‐based training programme. Issue 4 (16th October 2019) - Coletti, Daniel J.; Yalakkishettar, Pratiksha; Alexandri, Maya; Block, Lauren; Martinez, Johanna; Fornari, Alice; Conigliaro, Joseph
Abstract: Rationale, aims, and objectives: Providing high‐quality primary care in patient‐centred medical homes (PCMHa) requires competencies that can only be provided by interprofessional (IP) education. The benefits of collaborative training have been documented for learners, but less is known about the perceptions of the clinical professionals who train the learners or the patients receiving IP primary care. This investigation compared stakeholder attitudes about IP education, training, and providing collaborative care prior to developing a new IP training programme. Methods: We conducted five focus groups at a large general internal medicine training practice. Learner and faculty groups included participants from medicine, psychology, pharmacy, and physician assistant professions; three patient groups were held to obtain perspectives on receiving health care from IP trainees. We used inductive analysis to identify themes across the three stakeholder groups. Results: We identified seven convergent themes across all three stakeholder groups: (a) team engagement, (b) technology in care delivery, (c) cost of care, (d) involving patients in learning, (e) time constraints, (f) scope of practice, and (g) autonomy/interdependence. Each group emphasized the need to define and communicate team members' roles. Learners anticipated high‐quality IP interactions, and patients noted the benefits of receiving care from well‐supervised trainees. Faculty struggled to navigate the training needs of diverse learner groups and to integrate PCMH mandates focused on documentation with authentic patient‐centred care. Conclusions: This is the first reported data comparing perceptions about IP training and care across these three stakeholder groups. Results suggest the need to clarify scope of practice, define professional roles, and bridge gaps between teaching PCMH principles and subsequently providing high‐quality health care. Results inform faculty development needs in learning ways to train learners across professions and outline ways to structure interactions with patients.